Directing Ōta Shōgo’s Elements: From Form to Body - Lichtenfels, Peter (Performance Matters, 2024)
Peter Lichtenfels and Ōta Shōgo co-worked on the play Plastic Rose (1994) and had an understanding that there was no “pure” way of “doing Japanese theatre.” Ōta presented Lichtenfels with scripts of many of his plays and asked him to continue directing them. Through a study of two of Lichtenfels’ productions of Ōta’s play Elements—one produced in Davis, California (2017) and the other in Bogotà, Colombia (2018)—this essay explores insights arising from different theatre practices, some of the resonances, and three key issues of theatre directing that Ōta explores at a meta level in the play. With Elements, producing something on stage in the spirit of a different culture became a confidence that theatre bodies can work, within their contemporary possibilities or constraints, with the verbal, visual, and sound records of other embodied cultures. The scripts, those bodies, their voices, and their movements are resources on which transcultural theatre needs to draw before it happens into meaning.